Bone microstructure and volumetric bone mineral density in patients with hyperuricemia with and without psoriasis - Simon, David; Haschka, J.; Muschitz, C.; Kocijan, A.; Baierl, A.; Kleyer, Arnd; Schett, Georg; Kapiotis, S.; Resch, H.; Sticherling, Michael; Rech, Jürgen; Kocijan, R. (Osteoporosis international, 2020)
Summary: We analyzed volumetric bone mineral density (vBMD) and bone microstructure using HR-pQCT in subjects with normouricemia (NU) and subjects with hyperuricemia (HU) with and without psoriasis (PSO). HU was associated with higher cortical vBMD and thickness. Differences in average and trabecular vBMD were found between patients with PSO + HU and NU. Introduction: Hyperuricemia (HU) and gout are co-conditions of psoriasis and psoriatic arthritis. Current data suggest a positive association between HU and areal bone mineral density (BMD) and a negative influence of psoriasis on local bone, even in the absence of arthritis. However, the influence of the combination of HU and psoriasis on bone is still unclear. The aim of this study was to assess the impact of HU with and without psoriasis on bone microstructure and volumetric BMD (vBMD). Methods: Healthy individuals with uric acid levels within the normal range (NU), with hyperuricemia (HU), patients with hyperuricemia and psoriasis (PSO + HU), and patients with uric acid within the normal range and psoriasis (PSO + NU) were included in our study. Psoriasis patients had no current or past symptoms of arthritis. Average, trabecular, and cortical vBMD (mgHA/cm3); trabecular number (Tb.N, 1/mm) and thickness (Tb.Th, mm); inhomogeneity of the network (1/N.SD, mm); and cortical thickness (Ct.Th., mm) were carried out at the ultradistal radius using high-resolution peripheral quantitative computed tomography. In addition, bone turnover markers such as DKK-1, sclerostin, and P1NP were analyzed. Results: In total, 130 individuals were included (44 NU participants (34% female), 50 HU (24%), 16 PSO + HU (6%), 20 PSO + NU (60%)). Subjects were aged: NU 54.5 (42.8, 62.1), HU 57.5 (18.6, 65.1), PSO + HU 52.0 (42.3, 57.8), and PSO + NU 42.5 (34.8, 56.8), respectively. After adjusting for age, sex, BMI, and diabetes, patients in the HU group revealed significantly higher values of cortical vBMD (p < 0.001) as well as cortical thickness (p = 0.04) compared to the NU group. PSO + NU showed no differences to NU, but PSO + HU demonstrated both lower average (p = 0.03) and trabecular vBMD (p = 0.02). P1NP was associated with average, cortical, and trabecular vBMD as well as cortical thickness while sclerostin levels were related to trabecular vBMD. Conclusion: Hyperuricemia in otherwise healthy subjects was associated with a better cortical vBMD and higher cortical thickness. However, patients with both psoriasis and hyperuricemia revealed a lower vBMD.
CRIS-Team Scopus Importer:2020-01-21
Keywords: Bone Mineral Density; HR-pQCT; Hyperuricemia; Psoriasis